Levels of physical exercises and body composition predicting childhood obesity in schoolchildren Spaniards from the Mediterranean basin - Jose Antonio Latorre,; Leticia Heras Gonzalez,; Maria Jose Jimenez-Casquet,; Fatima Olea-Serrano,; Mariscal-Arcas, Miguel (Progress in Nutrition, 2021)
Background: Although a predisposition to obesity may be in part genetic, contributing factors include excess energy consumption, lack of physical activity, sleep deprivation, and more stable temperatures at home, among other characteristics of modern life. Aim: To evaluate the influence on obesity ofactivity/sedentariness and daily energy intake, using physical activity and semi-quantitative food frequency questionnaires. Methods:We enrolled 657 schoolchildren (53.5% girls) aged between 7 and 10 years in the Mediterranean Basin, Spain; 10.9% were obese. We examined the influence of the sports/total activity and energy intake of the children on their weight control. Results: No extracurricular sports activity was performed by 27.4% of the children, and this percentage was slightly but significantly higher for the girls. Among team sports, soccer was played by 36.9% of the schoolchildren and by a significantly higher percentage of boys than girls, we found a significantly higher likelihood of normal weight with sports practice/day (OR= 1.686), expenditure in sedentary activities (OR= 5.108), and total energy expenditure/day (OR= 3.686). Conclusions: Further research is warranted on the influence of physical activity and the family environment on the risk of overweight/obesity.